2019
DOI: 10.3390/microorganisms7100410
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics in Rumen Bacterial Community Composition of Finishing Steers during an Adaptation Period of Three Months

Abstract: The objective of this study was to explore whether collecting rumen samples of finishing steers at monthly intervals differed, and whether this difference or similarity varied with diets. For these purposes, 12 Chinese Holstein steers were equally divided into two groups. The dietary treatments were either standard energy and standard protein (C) or low energy and low protein (L). Rumen samples were obtained on day 30, day 60 and day 90 from both dietary treatments and were analyzed by using 16S rRNA gene sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…The predominant microbiota was quite different in seasons and opposite variation trend of Bacteroidetes abundance was observed in summer and winter [10]. Previous report revealed that both Succinivibrionaceae_UCG-002 and Ruminobacter abundances in rumen were positively associated with ambient temperature [8]. Yadav et al [11] found that low ambient temperature reduced the mean retention time of ruminal contents, thus low digestibility of digesta may appear.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The predominant microbiota was quite different in seasons and opposite variation trend of Bacteroidetes abundance was observed in summer and winter [10]. Previous report revealed that both Succinivibrionaceae_UCG-002 and Ruminobacter abundances in rumen were positively associated with ambient temperature [8]. Yadav et al [11] found that low ambient temperature reduced the mean retention time of ruminal contents, thus low digestibility of digesta may appear.…”
Section: Introductionmentioning
confidence: 93%
“…One hundred and twenty-six ruminal samples (42 samples from each fattening phase, with 4, 5, and 5 in H, C, and L diets, respectively) were extracted using a DNA Kit (OMEGA, Omega Bio-Tek, Norcross, GA, USA) as described by Qiu et al [8]. Purity and quality of genomic DNA were checked on 1% agarose gels and quantified using a spectrophotometer (NanoDrop 2000 Technologies Inc., Wilmington, DE, USA).…”
Section: Dna Extraction and Volatile Fatty Acids (Vfa) Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a core microbial community in the rumen [6,7], a large number of studies have reported that the rumen microbiome can be changed drastically by many factors, such as age [8][9][10], dietary source [11,12], feeding system [13][14][15], host species [7] and even geography [7]. For example, Wang et al investigated the temporal dynamics of the rumen microbiome in goats, and observed that the relative abundance of Firmicutes did not vary with age [9].…”
Section: Introductionmentioning
confidence: 99%